Digital watermarking in 2D and 3D transform domains focusing on fidelity and robustness / Almas Abbasi - Almas, Abbasi (2015)

(untitled)
Digital watermarking technique has been used to deal with issues like copyright protection and authentication to protect legitimate right of the owner and prevent illicit attempt to supersede it by the adversaries. These issues have become a matter of concern due to pervasive usage of digital media at various platforms in recent years. Robust watermarking techniques are usually applied for copyright protection, content authentication and temper localization because it can resist various kinds of manipulations on it. There is a need of developing a truly robust watermark to handle complicated and complex attacks. In this thesis, we focus on geometrically robust watermarking techniques especially invariant domain based technique for digital images. Additionally, we also studied schemes for three dimensional (3D) image representation named Depth Image Based Rendering (DIBR). We have proposed a robust dynamic block based watermarking technique in 2D domain using Genetic Programming (GP) to achieve imperceptibility and robustness. This technique can embed an imperceptible and robust watermark in images irrespective of the size of the blocks. We present a GP based perceptual shaping function which determines the optimal watermark strength for the selected coefficients using Human Visual System characteristics (HVS) such as luminance sensitivity, and self and neighborhood contrast masking. Our proposed scheme can resist image processing attack, noise attack, geometric attack and cascading attack. Comparison results show that our dynamic block based technique is approximately 5% and 23% more robust than the other two compared techniques. In addition, we proposed two new invariant domain based watermarking techniques. They are Rotation, Scaling and Translation (RST) invariant domain based on Riesz Transformation (RT), and fractional calculus based polynomial watermarking domain. We are the first to explore invariant properties of RT, fractional sinc and fractional Heaviside function. The advantage of invariant domain based watermarking techniques is they do not need resynchronization step for the watermark detection. It results in less processing time, and less distortion induced due to resynchronization process. We also extended watermarking from two dimension (2D) environment to 3D scenario. We have proposed an imperceptible and robust watermarking scheme in Multi- Dimensional Wavelet Transformation (MDWT) domain for the content protection of 3D DIBR. Interval Type-2 Fuzzy Logic System (IT2FLS) is used to determine the weight factor using noise visibility and entropy value to embed watermark imperceptibly. The proposed technique embeds watermark with least distortion in the rendered left and rendered right images for imperceptibility. The experimental results show that the proposed technique is robust against JPEG compression, depth image alteration, Gaussian noise and rotation attacks. Moreover, the bit error rate (BER) of the extracted watermark is nearly negligible.